Między Rzymem a prowincją. O opowieściach rzymskich Józefa Ignacego Kraszewskiego - Szczot, Monika (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
The ai mof the article is to analyse Józef Ignacy Kraszewski's Roman novels in the aspect of presenting two spaces: Rome and the provinces. The valuation of space takes place on different planes of the works: the descriptive plane, the scenery and the metaphorical plane. The scenery describes the space and characterises the characters associated with it. Metaphorical meanings are realised through topics, symbols and motifs that allow the sphere of sacrum to exist, deepening the ideological meaning of the novels.
Keywords: Prowincja; Rzym; powieść historyczna; przestrzeń